Profil perdarahan uterus abnormal di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2013 – 31 Desember 2014 - Rifki, Muhammad; Loho, Maria; Wagey, Frank M.M (Universitas Sam Ratulangi, 2016)
Abstract: Abnormal Uterine Bleeding (AUB) is the most common cause of abnormal vaginal bleeding among women in reproductive age. Approximately 30% of women come to health care center with complaints of AUB during their reproductive period. The causes of AUB include a broad spectrum of diseases. The main classification of AUB according to FIGO has 9 categories of causes that is the acronym as